Highly reflective nc-Si:H/a-CNx:H multilayer films prepared by r.f. PECVD technique - Ritikos, R.; Goh, B.T.; Sharif, K.A.M.; Muhamad, M.R.; Rahman, S.A. (2009)
Multilayer thin films consisting of a-CNx:H/nc-Si:H layers prepared by radio-frequency plasma enhanced chemical vapour (r.f, PECVD) deposition technique were studied. High optical reflectivity at a specific wavelength is one of major concern for its application. By using this technique, a-CNx:H/nc-Si:H multilayered thin films (3-11 periods) were deposited on substrates of p-type (111) crystal silicon and quartz. These films were characterized using ultra-violet-visible-near infrared (UV-Vis-NIR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, field effect scanning electron microscopy (FESEM) and AUGER electron spectroscopy (AES). The multilayered films show high reflectivity and wide stop band width at a wavelength of approximately 650 +/- 60 nm. The FTIR spectrum of this multilayered structure showed the formation of Si-H and Si-H-2 bonds in the nc-Si:H layer and C=C and N-H bonds in a-CNx:H layer. SEM image and AES reveal distinct formation of a-CNx:H and nc-Si:H layers in the cross section image with a decrease in interlayer cross contamination with increasing number of periods. (c) 2009 Elsevier B.V. All rights reserved.